Craniofacial growth studies in orthodontic research - lessons, considerations and controversies - Wishney Morgan; Darendeliler M. Ali; Dalci Oyku (Sciendo, 2018)
The distinguishing features of Class I, Class II and Class III craniofacial growth have been subjects of orthodontic research since the middle of the 20th century. However, the moral and practical issues related to studying craniofacial growth in modern times have presented unresolved challenges to researchers. While previous longitudinal growth investigations are typically based on historical data sets, the cephalometric growth studies of contemporary populations must now rely on cross-sectional data. Furthermore, clinical orthodontic research has faced similar ethical challenges in which therapeutic outcomes are analysed using historical control data. These limitations, amongst others, have obscured the conclusions that can be drawn from both types of studies. This article begins with a review of the defining characteristics of Class I, Class II and Class III growth and then explores the limitations of growth studies and the use of historical control groups in orthodontic research.